The use of immersive virtual reality (VR) to predict the occurrence 6 months later of paranoid thinking and posttraumatic stress symptoms assessed by self-report and interviewer methods: a study of individuals who have been physically assaulted. - Freeman, D; Antley, A; Ehlers, A; Dunn, G; Thompson, C; Vorontsova, N; Garety, P; Kuipers, E; Glucksman, E; Slater, M (2014)
Presentation of social situations via immersive virtual reality (VR) has the potential to be an ecologically valid way of assessing psychiatric symptoms. In this study we assess the occurrence of paranoid thinking and of symptoms of posttraumatic stress disorder (PTSD) in response to a single neutral VR social environment as predictors of later psychiatric symptoms assessed by standard methods. One hundred six people entered an immersive VR social environment (a train ride), presented via a head-mounted display, 4 weeks after having attended hospital because of a physical assault. Paranoid thinking about the neutral computer-generated characters and the occurrence of PTSD symptoms in VR were assessed. Reactions in VR were then used to predict the occurrence 6 months later of symptoms of paranoia and PTSD, as assessed by standard interviewer and self-report methods. Responses to VR predicted the severity of paranoia and PTSD symptoms as assessed by standard measures 6 months later. The VR assessments also added predictive value to the baseline interviewer methods, especially for paranoia. Brief exposure to environments presented via virtual reality provides a symptom assessment with predictive ability over many months. VR assessment may be of particular benefit for difficult to assess problems, such as paranoia, that have no gold standard assessment method. In the future, VR environments may be used in the clinic to complement standard self-report and clinical interview methods.